A Comprehensive Review of Production, Nutritional Value and Toxicity of Kawal, a Fermented Product from Leaves of Cassia obtusifolia (L.) - Fangbo, Amboussidi; Wilfred, Ngaha Damndja; Joseph, Collinlaw Ndouyang; Mbaiguinam, Mbailao; Nicolas, Njintang Yanou (Contemporary Research and Perspectives in Biological Science Vol. 11, 2025)
Cassia obtusifolia, is a plant of the Fabaceae family. Its leaves are eaten as a vegetable in several African countries. In some African countries like Chad and Sudan, the leaves are processed by fermentation in a solid state, called Arabic kawal, which is eaten with cereal couscous. Kawal is a good source of protein, calcium, potassium, magnesium and vitamin C. The objective of this review is to analyze the technology of production and the nutritional value of kawal. The production technology of kawal which is done under natural conditions is underpinned by microorganisms responsible for the fermentation of C. obtusifolia leaves. This review examines the literature on kawal production and similar fermented products. The production of kawal remains made by craftsmen. After crushing, the leaves are incubated in a buried jar for a period that varies from 14 to 30 days, sun-dried for 3 to 5 days and ready for consumption. Kawal has several nutritional benefits and fermentation increases protein content by 38% and especially essential amino acids methionine, threonine, valine, isoleucine, arginine, by 15, 51, 17, 113 and 3% respectively. Also, during the processing of kawal, minerals content is improved, in particular calcium, magnesium and iron which increase by 98, 75 and 47% respectively. Concerning secondary metabolites, fermentation applied to C. obtusifolia leaves reduces the level of polyphenols, tannins and phytic acid by 20, 6 and 47% respectively. However, some studies on the effect of kawal on albino rats and chicken growth have revealed signs of toxicity manifested through high levels of serum transaminases and histopathology of the liver and kidneys. These data show that the fermentation of C. obtusifolia leaves improves the nutritional value of this vegetable but does not considerably reduce secondary metabolites which could be considered anti-nutrients and might be responsible for the toxicity in albino rats and chickens. This review concluded that the technology greatly influences the biochemical and nutritional quality of kawal by improving the protein and mineral content on one hand and reducing the level of secondary metabolites on the other. However, there are aspects of kawal that have not been subjected to studies, notably the practices during production by the producers and the sensory analysis of kawal, which need to be investigated for more information on this food product.